Bushen Huoxue Attenuates Diabetes-Induced Cognitive Impairment by Improvement of Cerebral Microcirculation: Involvement of RhoA/ROCK/moesin and Src Signaling Pathways - Li, Yuan; Li, Quan; Pan, Chun-Shui; Yan, Li; Hu, Bai-He; Liu, Yu-Ying; Yang, Lei; Huang, Ping; Zhao, Shao-Yang; Wang, Chuan-She; Fan, Jing-Yu; Wang, Xue-Mei; et al. (Frontiers in Physiology, 2018)
Type 2 Diabetes mellitus (T2DM) is closely correlated with cognitive impairment and neurodegenerative disease. Bushen Huoxue (BSHX) is a compound Chinese medicine used clinically to treat diabetes-induced cognitive impairment. However, its underlying mechanisms remain unclear. In the present study, KKAy mice, a genetic model of type 2 diabetes with obesity and insulin resistant hyperglycemia, received a daily administration of BSHX for 12 weeks. Blood glucose was measured every four weeks. After 12 weeks, BSHX treatment significantly ameliorated the T2DM related insults, including the increased blood glucose, the impaired spatial memory, decreased cerebral blood flow (CBF), occurrence of albumin leakage, leukocyte adhesion and opening capillary rarefaction. Meanwhile, the downregulation of the tight junction proteins (TJ) claudin-5, occludin, zonula occluden-1 (ZO-1) and JAM-1 between endothelial cells, amyloid-β (Aβ) accumulation in hippocampus, increased AGEs and RAGE, and expression of RhoA/ROCK/moesin signaling pathway and phosphorylation of Src kinase in KKAy mice were signiﬁcantly protected by BSHX treatment. These results indicate that the protective effect of BSHX on T2DM-induced cognitive impairment involves regulation of RhoA/ROCK1/moesin signaling pathway and phosphorylation of Src kinase.